Doctors’ satisfaction with the rehabilitation system for anti-terrorist operation participants: A factor analysis - Irina Holovanova; Oleksandr Havlovsky; Shanshan Wang; Oleksandr Korneta; Maksym Khorosh; Igor Kaydashev; Renee Robinson; Ubydul Haque (Heliyon)
Background: A war has a catastrophic effect on veterans’ health. However, there is a knowledge gap about the veterans’ rehabilitation system, requirements, and the satisfaction of doctor-organizers. The present study aims to assess the level of satisfaction of the doctor-organizers of health care with the existing rehabilitation system for anti-terrorist operation (ATO) veterans in Ukraine. Methods: A cross-sectional design was conducted during the ATO in March–April 2020. A total of 25 organizing doctors from healthcare institutions filled out the form. The questionnaire consisted of three blocks: 1) Main characteristics of the existing system of rehabilitation of ATO veterans (14 items); 2) Strengths of the existing system of rehabilitation of ATO veterans (11 items); and 3) Weaknesses of the existing system of rehabilitation of ATO veterans (8 items). Evaluation of the rehabilitation system was carried out using factor analysis. Results: The main features of the system were accessibility, financing of rehabilitation programs, and commitment to the rehabilitation of ATO veterans. The advantages of the system included 1) doctors and organizers identifying the regulatory and legal provision of medical and social protection for the rehabilitation of veterans, 2) access to experienced personnel to carry it out, 3) respectful attitude towards veterans, and 4) comprehensive rehabilitation. In addition, disadvantages inherent in the system included: 1) violation of the integral principle, 2) insufficient material, technical support, and financial resources for rehabilitation programs, and 3) legislative and regulatory gaps necessary to provide rehabilitation to ATO veterans. Conclusions: The findings provided healthcare organizers with information on the main features, advantages, and disadvantages of the rehabilitation of ATO veterans. These insights can aid in optimizing the current rehabilitation system in Ukraine.